Genetically programmed changes in transcription of the novel progranulin regulator - Keller, Maria (J Mol Med (Berl), 2020)
ABSTRACT: Progranulin is a glycoprotein marking chronic inflammation in obesity and type 2 diabetes. Previous studies suggested PSRC1 (proline and serine rich coiled-coil 1) to be a target of genetic variants associated with serum progranulin levels. We aimed to identify potentially functional variants and characterize their role in regulation of PSRC1. Phylogenetic module complexity analysis (PMCA) prioritized four polymorphisms (rs12740374, rs629301, rs660240, rs7528419) altering transcription factor binding sites with an overall score for potential regulatory function of S(all) > 7.0. The effects of these variants on transcriptional activity and binding of transcription factors were tested by luciferase reporter and electrophoretic mobility shift assays (EMSA). In parallel, blood DNA promoter methylation of two regions was tested in subjects with a very high (N = 100) or a very low (N = 100) serum progranulin. Luciferase assays revealed lower activities in vectors carrying the rs629301-A compared with the C allele. Moreover, EMSA indicated a different binding pattern for the two rs629301 alleles, with an additional prominent band for the A allele, which was finally confirmed with the supershift for the Yin Yang 1 transcription factor (YY1). Subjects with high progranulin levels manifested a significantly higher mean DNA methylation (P < 1 × 10(−7)) in one promoter region, which was in line with a significantly lower PSRC1 mRNA expression levels in blood (P = 1 × 10(−3)). Consistently, rs629301-A allele was associated with lower PSRC1 mRNA expression (P < 1 × 10(−7)). Our data suggest that the progranulin-associated variant rs629301 modifies the transcription of PSRC1 through alteration of YY1 binding capacity. DNA methylation studies further support the role of PSRC1 in regulation of progranulin serum levels. KEY MESSAGES: PSRC1 (proline and serine rich coiled-coil 1) SNPs are associated with serum progranulin levels. rs629301 regulates PSRC1 expression by affecting Yin Yang 1 transcription factor (YY1) binding. PSRC1 is also epigenetically regulated in subjects with high progranulin levels. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00109-020-01942-7) contains supplementary material, which is available to authorized users.